2022
DOI: 10.18240/ijo.2022.12.12
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical effects of intravitreal injections of conbercept for the treatment of choroidal neovascularization in patients with pathological myopia

Abstract: AIM: To observe the long-term clinical efficacy of intravitreal injections of conbercept, a novel vascular growth factor inhibitor, for the treatment of pathological myopia choroidal neovascularization (PM-CNV). METHODS: A total of 67 eyes (from 67 patients; mean age, 54.90±12.7y) with PM-CNV were retrospectively researched. Based on the different schemes used for the administration of the drug, the patients were divided into two groups: group A (n=35; average age, 53.31±13.6y; average diopter, 9.25±1.72 D), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…No patient developed RD according to 2 studies in the office setting and 1 study in the OR, whereas another study reported an RD rate of 0.003% in the OR. Two studies in the office setting gave a combined incidence rate of 0.01% and 0.02% for vitreous hemorrhage and RT, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No patient developed RD according to 2 studies in the office setting and 1 study in the OR, whereas another study reported an RD rate of 0.003% in the OR. Two studies in the office setting gave a combined incidence rate of 0.01% and 0.02% for vitreous hemorrhage and RT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies are detailed in eTable 1 in the Supplement. Seventeen studies reported a total of 944 765 injections administered in the office setting, while 14 studies reported 302 039 injections administered in the OR . Only 2 studies directly compared office-based injections with the OR-based injections: Abell et al reported no significant difference in age, sex, ocular comorbidities, or socioeconomic status between the 2 injection settings, while Tabandeh et al indicated similar baseline diagnosis; patients in both studies were injected with ranibizumab or bevacizumab.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations